DEVELOPING AN ENGLISH SYLLABUS FOR STUDENTS OF LAW AT JAMBI UNIVERSITY - yanto yanto; Sri Lestari; Tubagus Zam Zam Al Arif (Universitas Jambi, 2019)
The objective of this study is to develop an English syllabus for undergraduate students of law at the University of Jambi. The subjects therefore involve students of law at the second semester. To get the data of student needs, the questionnaire and interview were implemented in this research. Research and Development were adopted as the research design while the model of develop used instructional design by Branch. The most important stage in this study is to investigate the language needs of students of law. It was done by distributing questionnaires to the students and interviewing them. The develop phases cut off the implement and evaluate phase. Therefore, the study ended up in develop phase. This study proposed to develop a suggested English syllabus for law due to the importance to improve quality of teaching non English department students by renewing the information of student needs as it changes for following the demands of epoch.